The role of HDL in plaque stabilization and regression: basic mechanisms and clinical implications. Issue 7 (November 2016) - Feig, Jonathan E.; Feig, Jessica L.; Dangas, George D.
Abstract : On the basis of studies that extend back to the early 1900s, regression and stabilization of atherosclerosis in humans has progressed from being a concept to one that is achievable. Successful attempts at regression generally applied robust measures to improve plasma lipoprotein profiles. Possible mechanisms responsible for lesion shrinkage include decreased retention of atherogenic apolipoprotein B within the arterial wall, efflux of cholesterol and other toxic lipids from plaques, emigration of lesional foam cells out of the arterial wall, and influx of healthy phagocytes that remove necrotic debris as well as other components of the plaque. Currently available clinical agents, however, still fail to stop most cardiovascular events. For years, HDL has been considered the 'good cholesterol.' Clinical intervention studies to causally link plasma HDL-C levels to decreased progression or to the regression of atherosclerotic plaques are relatively few because of the lack of therapeutic agents that can selectively and potently increase HDL-C. The negative results of studies that were carried out have led to uncertainty as to the role that HDL plays in atherosclerosis. It is becoming clearer, however, that HDL function rather than quantity is most crucial and, therefore, discovery of agents that enhance the quality of HDL should be the goal.